Development and design of raised irrigation plots for improved drainage in areas of high water table - Kumar, Rakesh; Apichart Anukularmphai; I, Fude; Nielsen, Jens Moller; Government of Belgium (Bangkok : Asian Institute of Technology, 1977)
A field experiment was conducted· at the Asian Institute of Technology during March 1977 to investigate the effect of high water table for Chinese cabbage, Chinese green and lettuce vegetable crops. The plots were raised to 30, 40 and 50 ems from the ditch water table. The soil permeability, soil nutrients (N, P and K) , soil pH, electrical conductivity and pH of ditch water were analyzed in the laboratory. The chemical composition of plants, various nutrients such as N, P, K, Ca, Mg and Na were also analyzed. The growth and yield measurements were made for all plots separately. Raised beds of 30 ems height from the ditch water level had been found to give maximum yield for these crops; because the soil nutrients were easily available to the plants in those terraces. From water table and root depth measurements it is quite clear that the height of terrace can be reduced to even 25 ems. Based on the experimental results obtained, it was found that Hooghout's formula gave good results H for spacing and water table height. The soil nutrients N, P, K, soil p , electrical conductivity of ditch water, pH of ditch water and electrical conductivity of soil have decreased during the experimental period.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology,1977
Keywords: Plant-water relationships; Plant-soil relationships; Drainage research